Analysis of Factors Influencing Nematode Prevalence in Beef Cattle Faeces at Tanjung Morawa District - Fantari, E.; M. Tafsin; N. Ginting; P. Patriani; A. Purba (Talenta Publisher, 2023)
This study aims to identify the type, number of nematode eggs, and nematode prevalence rate, as well as determine the factors that influence the prevalence of nematode eggs in beef cattle feces in Tanjung Morawa District. The research method used was direct interviews with farmers assisted by questionnaires and examination of 89 beef cattle fecal samples at the Medan Veterinary Center Parasitology Laboratory. Purposive sampling techniques were carried out. The research samples were Dalu Sepuluh A Village, Bangun Rejo Village, Dalu Sepuluh B Village in Tanjung Morawa District with variables maintenance systems, deworming, cage sanitation, forage collection time, cow age, cattle breed, and gender. Based on the examination results, 43 positive samples were obtained with a prevalence of 48.31% (commonly), and the egg infestation rate per gram of feces was in the low to medium category, with an average of 200-700 eggs. The types of nematode eggs found are Bunostomum sp., Capillaria sp., Cooperia sp., Eimeria sp., Oesophagostomum sp., Trichuris sp. Most nematode eggs are in the type of Eimeria sp. Factors influencing the prevalence and infestation of eggs per gram of feces are the maintenance system, deworming, cage sanitation, and forage collection time.